Improving immunological insights into the ferret model of human viral infectious disease. Issue 6 (3rd October 2019) - Wong, Julius; Layton, Daniel; Wheatley, Adam K.; Kent, Stephen J.
Abstract: Ferrets are a well‐established model for studying both the pathogenesis and transmission of human respiratory viruses and evaluation of antiviral vaccines. Advanced immunological studies would add substantial value to the ferret models of disease but are hindered by the low number of ferret‐reactive reagents available for flow cytometry and immunohistochemistry. Nevertheless, progress has been made to understand immune responses in the ferret model with a limited set of ferret‐specific reagents and assays. This review examines current immunological insights gained from the ferret model across relevant human respiratory diseases, with a focus on influenza viruses. We highlight key knowledge gaps that need to be bridged to advance the utility of ferrets for immunological studies.